Evaluation of the Iraqi Media Network's Proposed Strategy for the Period (2024-2028) - Mahmood Ibrahim*, Aous; Aftan Abdullah, Yousif (Journal of Economics and Administrative Sciences, 2024)
The strategy of the Iraqi media network has faced a significant challenge during the recent decades due to instability resulting from the political and security conditions experienced by Iraq. This deeply impacts various aspects of life,  especially the media industry. In light of these circumstances, the idea of evaluating the proposed strategy for the Iraqi media network has emerged.The current research aims to study a crucial phase of strategic management, strategic evaluation, to assess the proposed strategy through data analysis, ensuring its implementation with minimal deviation from the planned course. The study focuses on studying and evaluating the proposed strategy for the Iraqi media network for the years 2024-2028, examining its effectiveness and alignment with the state's directions. That involves understanding the realism of strategic visions, plans, and programs and building a suitable conceptualization.This research focuses on environmental conditions and relies on scientific foundations and steps to formulate and evaluate the strategy. We created a study of senior figures, including general managers and experts in the Iraqi Media Network, 15 of whom purposefully selected the experts most relevant to the strategy and those responsible for evaluating it.The research hypothesis suggests a consensus among the network's managers and experts on the proposed strategy for the next five years in all its dimensions. The research results indicate that the reality of plans, programs, and visions is very good, developed by experienced leaders capable of evaluating the proposed strategy. The findings also demonstrate obvious acceptance of the strategy by the research sample and alignment with the proposed strategic alternative. Research Type: Research Paper